Surgical Result of Goniotomy on Primary Congenital Glaucoma in Indonesia Patient - Arini Akbar; Virawardhana Istiantoro; Florence Manurung (Majalah Oftalmologi Indonesia, 2021)
Objective: To present a case of goniotomy procedure and angle imaging on primary congenital glaucoma (PCG) in Indonesian patient.Case presentation: a 6 month old baby presenting with enlarged left eye since birth. The ophthalmological examination found good light and object fixation on both eyes. The eyes were orthophoric. There was no nystagmus and movement restriction. The corneal diameter of the right eye was 10 mm and the left eye was 13 mm. Haab striae (+) on left eye. The intraocular pressure (IOP) was 11 mmHg on right eye and 35 mmHg on left eye. There were no other abnormalities on both eyes. A goniotomy procedure was done on the left eye. The IOP of the left eye on 1 day, 1 week and 3 month post surgery were 6, 18 and 17 mmHg respectively. The cornea of the left eye was clear despite the Haab striae dan bruckner test was good. Optic nerve head examination of the left eye was good and the cup to disk ratio was 0.5.Conclusions: Surgical therapy is usually warranted in the management of PCG. Goniotomy is typically chosen as the initial surgery when the refractive media is clear and direct visualization of the angle is visible. The advantage of goniotomy over other angle surgeries for PCG is spare of the conjunctiva for filtration surgery if required in the future. Our case of goniotomy on PCG in Indonesian patient showed good results and promising prognosis post procedure.